EFFECT OF PALM OIL BUDLE ASH ON REDUCTION OF OIL/FAT HOSPITAL WASTEWATER - Defi Ermayendri; Yusmidiarti Yusmidiarti (Poltekkes Kemenkes Bengkulu, 2022)
Activities in healthcare facilities have a negative impact in the form of pollution due to waste disposal without proper processing. One of the most dangerous is lipid or fat waste in wastewater. Lipids are also a threat to the aquatic environment, such as those found in ditches and rivers. Oil/fat will cause pollution in the river and in the processing plant itself thereby reducing the efficiency of wastewater treatment. Oil and grease removal usually uses physical methods, namely by trapping oil/fat with a grease trap. The second uses a flotation process utilizing the force of gravity. It is hoped that the ash of empty palm fruit bunches can be used to reduce the oil/fat content in hospital wastewater as another alternative to set aside oil and grease. This research was conducted to determine the relationship between quantitative variables to determine the model to be used. The distribution of the dots on a scatter plot chart can show the relationship between variables. The relationship studied is in the form of patterns that are observed visually and to obtain correlation determinants and equations (models) of the relationship between variables through scatter plot graphics. The results of this study indicate that there is a relationship between the addition of empty palm fruit bunch ash to the reduction of oil and fat. Adding 0.1 mg.l-1 of empty palm fruit bunch ash resulted in an average decrease in oil and fat content of 60.34%; The addition of 0.2 mg.l-1 resulted in a decrease of 75.38% and the addition of 0.5 mg.l-1 after a decrease of 90.42%. To reduce the oil and fat content to 0 (zero) (perfect emulsion) to 3.25 mg.l-1 sample from the simple regression equation (y = -4.8969x + 2.3919) is 0.47 g/liter of waste water or 0 .47 kg/m3 of wastewater.